Complete Regression of Endobronchial Carcinoid Tumor after an Endoscopic Biopsy - Saeki, Kazuhiko; Moritaka, Tomonori; Inoue, Koji; Kondo, Haruka; Nakanishi, Norihiko; Tachibana, Sayaka; Katsuta, Tomoya; Nakamura, Junya; Morimoto, Kojiro (Internal Medicine, 2023)
An 80-year-old woman who had been diagnosed with an endobronchial carcinoid tumor visited our hospital for treatment with an endoscopic technique. However, a bronchoscopic examination at our hospital showed spontaneous regression of the tumor at the orifice of the right middle lobar bronchus. Chest computed tomography five months later revealed no local recurrence. This is the second report of an endobronchial carcinoid tumor vanishing after an endoscopic biopsy.